Self-enhancement or Self-transcendence? Enriching Baumol's Concept of Productive Entrepreneurship Using the Biblical Narrative - Rietveld, Cornelius A.; van der Kooi, Cornelis; Slob, Henri (Senate Hall, 2021)
Policy makers and entrepreneurs increasingly use storytelling to nurture cultures inside and outside organizations. In this article, we explore how the biblical narrative in which God is characterized by a lasting entrepreneurial commitment to achieve "win-win" situations may inspire commercial entrepreneurs to take actions in which they transcend their own utility maximization in order to let other stakeholders (e.g., their employees) flourish. We argue that such self-transcendence, in contrast to self-enhancement, is an important but overlooked element of productive entrepreneurship. As such, by drawing on the biblical narrative, we enrich Baumol's seminal conceptualization of productive entrepreneurship. We explore and illustrate the ecological validity of self-transcendence in commercial organizations using two case studies. The case studies underscore the power of narratives, and illustrate the potentiality of entrepreneurial self-transcendence in commercial organizations and its possible consequences.
Keywords: Baumol|entrepreneurship|storytelling|biblical narrative